Pemanfaatan Budidaya Lele Sebagai Pemberian Makanan Tambahan (PMT) untuk Peningkatan Gizi Balita dalam Pencegahan Stunting Melalui Program Genting - Pradnyani, Ni Luh Kadek Ardhia Swari; Meilawaty, Zahara; Ziaulhaq, Mochamad Najib; Nabilla, Purry Roro; Alisah, Putri Alisah (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Stunting, a developmental disorder in children caused by chronic malnutrition and recurrent infections, characterized by below-standard height, remains a critical issue for Indonesia. In Mayang Village, one of the communities supported by the University of Jember, 2.46% of the population experiences stunting. To address this issue, the PPK Ormawa Team of BEM FKG UNEJ developed a stunting prevention program utilizing catfish farming as a source of nutritionally balanced supplementary food, named GENTING (Mayang Village Movement Against Stunting). This initiative involves empowering integrated health post (posyandu) cadres through training in catfish cultivation and the processing of nutritionally balanced supplementary foods. The program outcomes include the production of supplementary food to meet the nutritional needs of toddlers in Mayang Village and the enhancement of knowledge and skills among posyandu cadres in stunting prevention